Isolated Bulbar Conjunctival Kaposi’s Sarcoma as a Primary Presentation of AIDS: A Case Report - Sofia Maia; Miguel Gomes; Luís Oliveira; Paulo Torres (Case Reports in Ophthalmological Medicine)
Kaposi’s sarcoma (KS) is a malignant vascular tumor, caused by the human herpesvirus 8. It is one of the commonest tumors in human immunodeficiency virus (HIV) patients and not uncommonly the first manifestation of acquired immunodeficiency syndrome (AIDS). Case. We present a case of an isolated bulbar conjunctival KS on a 43-year-old HIV positive male, with no other lesions. Excision and cryotherapy were performed, and the patient remains free of lesions to date. Conclusion. Isolated bulbar conjunctival KP is an unusual site for its initial presentation and must be kept in mind in HIV positive patients.